Alienated Social Class And Social Poverty: Case From Rural Hamlet Karang Tengah, West Java, Indonesia - Terserah Luahambowo; Robert M.Z. Lawang; Iwan Setiawan (STISIP Widuri Jakarta, 2021)
This article deals with fundamental question of how to develop village is based on sufficient knowledge. In order to answer this question, Research Cluster on Rural Issues has conducted digital baseline survey on village resources, potential for rural development in the hamlet of Karang Tengah. One of the findings is the fact that 88.3% of the land has been alienated to outsiders. The finding is explored through extensive discussions on social class theories related to social capital and social poverty as well. Alienated social class is a concept developed from the highly imbalance of outsiders’ domination to the insiders. As the result, community has been lack of its fundamental essence namely land. Main conclusions are related to the need of real knowledge through the use of digital survey for a quick answer.